2021
DOI: 10.18632/aging.203559
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 facilitates IL-1β production in osteoarthritis synovial fibroblasts by suppressing miR-204-5p synthesis through the AP-1 and NF-κB pathways

Abstract: The progression of osteoarthritis (OA) is mediated by adipokines, one of which is nesfatin-1, which is responsible for the production of inflammatory cytokines. However, how this molecule may affect the synthesis of the proinflammatory cytokine interleukin 1 beta (IL-1β) in OA is unclear. Our analyses of records from the Gene Expression Omnibus (GEO) dataset and clinical specimens of synovial tissue revealed higher levels of nesfatin-1 and IL-1β in OA samples compared with normal healthy tissue. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Studies have demonstrated that NF-κB is a key member of lipocalin 2-induced OA ( Guo et al, 2014 ; Conde et al, 2016 ). A novel adipokine, Nesfatin-1, was also found to stimulate NF-κB pathway ( Lee et al, 2021 ).…”
Section: Adipokine Signaling Pathways In Osteoarthritismentioning
confidence: 99%
“…Studies have demonstrated that NF-κB is a key member of lipocalin 2-induced OA ( Guo et al, 2014 ; Conde et al, 2016 ). A novel adipokine, Nesfatin-1, was also found to stimulate NF-κB pathway ( Lee et al, 2021 ).…”
Section: Adipokine Signaling Pathways In Osteoarthritismentioning
confidence: 99%
“…Controversy surrounds nesfatin-1 in arthritis diseases, as this adipokine exhibits both proinflammatory and anti-inflammatory functions. For example, nesfatin-1 can suppress IL-1β expression in OA chondrocytes and thus reduce the severity of cartilage destruction in OA rats 39 , but nesfatin-1 can also facilitate IL-1β expression in OA synovial fibroblasts 40 . Interestingly, nesfatin-1 shows protective effects in cartilage from rats with adjuvant-induced arthritis 41 and reportedly reduces the risk of atherosclerotic disease in patients with RA 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Controversy surrounds nesfatin-1 in arthritis diseases, as this adipokine exhibits both proin ammatory and anti-in ammatory functions. For example, nesfatin-1 can suppress IL-1β expression in OA chondrocytes and thus reduce the severity of cartilage destruction in OA rats (34), but nesfatin-1 can also facilitate IL-1β expression in OA synovial broblasts (35). Interestingly, nesfatin-1 shows protective effects in cartilage from rats with adjuvant-induced arthritis(36) and reportedly reduces the risk of atherosclerotic disease in patients with RA (37).…”
Section: Discussionmentioning
confidence: 99%